Endogenous Uteroglobin as Intrinsic Anti-inflammatory Signal Modulates Monocyte and Macrophage Subsets Distribution Upon Sepsis Induced Lung Injury - Janicova, Andrea; Becker, Nils; Xu, Baolin; Wutzler, Sebastian; Vollrath, Jan Tilmann; Hildebrand, Frank; Ehnert, Sabrina; Marzi, Ingo; Störmann, Philipp; Relja, Borna (Frontiers in Immunology, 2019)
Sepsis is a serious clinical condition with life-threatening organ dysfunction, and limited therapeutic options. The paradigm of limiting excessive inflammation and promoting anti-inflammatory responses is a simplified concept. Yet, the absence of intrinsic anti-inflammatory signalling at the early stage of an infection can lead to exaggerated activation of immune cells including monocytes and macrophages. There is emerging evidence that endogenous molecules control those mechanisms. Here we aimed to identify and describe the dynamic changes in monocyte and macrophage subsets and lung damage in CL57BL/6N mice undergoing blunt chest trauma with subsequent cecal ligation and puncture. We showed that early increase in systemic and activated Ly6C+CD11b+CD45+Ly6G- monocytes was paralleled by their increased emigration into lungs. The ratio of pro-inflammatory Ly6ChighCD11b+CD45+Ly6G- to patrolling Ly6ClowCD11b+CD45+Ly6G- monocytes significantly increased in blood, lungs and bronchoalveolar lavage fluid (BALF) suggesting an early transition to inflammatory phenotype during early sepsis development. Similar to monocytes, the level of pro-inflammatory Ly6ChighCD45+F4/80+ macrophages increased in lungs and BALF, while tissue repairing Ly6ClowCD45+F4/80+ macrophages declined in BALF. Levels of inflammatory mediators TNF-α and MCP-1 in blood and RAGE in lungs and BALF were elevated, and besides their boosting of inflammation by recruitment of cells, they may promote monocyte and macrophage polarization, respectively,b toward the pro-inflammatory phenotype. Neutralization of uteroglobin increased pro-inflammatory cytokine levels, activation of inflammatory phenotypes and their recruitment to lungs, concurrent with increased pulmonary damage in septic mice. In in vitro experiments, the influence of uteroglobin on monocyte functions including migratory behavior, TGF-β1 expression, cytotoxicity and viability were proved. These results highlight an important role of endogenous uteroglobin as intrinsic anti-inflammatory signal upon sepsis-induced early lung injury, which modules the early monocyte/macrophages driven inflammation.